Family financial management in household consumption among muslims in Johor - Mohamed Abu Baker, M Mohaideen (2025)
This study aims to evaluate family financial management in preventing unnecessary consumption among Muslim households. Poor financial planning, low financial literacy, and rising household debt are growing issues in Malaysia, especially among young Muslim families. Using a quantitative approach, primary data were collected through questionnaires distributed in Masai, Permas Jaya, and Pasir Gudang. The data were analyzed using SPSS version 29. Findings highlight five significant factors: household income, occupation, family background, financial literacy, and education level. The study supports the application of Islamic financial principles to guide responsible spending, avoid excessive debt, and promote effective household financial management in line with Islamic values.